Parametrization of prompt neutron yields from photofission fragments of actinide nuclei for the giant dipole resonance energy range - Lengyel, A.I.; Parlag, O.O.; Maslyuk, V.T.; Kibkalo, Yu.V.; Romanyuk, M.I. (Вопросы атомной науки и техники, 2014)
The dependence of prompt neutron yield on fragment mass ν(A) of photofission of actinide nuclei ²³²Th, ²³⁵U and ²³⁸U in the giant dipole resonance energy range has been parameterized. This allows us to describe the observed changes of saw-tooth behavior of neutron yield from the light and heavy fragments using few energy and nucleon composition dependent free parameters and to predict ν(A) for Pu isotopes. Выполнена параметризация зависимости выходов мгновенных нейтронов от массы осколков ν(A) фотоделения актинидных ядер ²³²Th, ²³⁵U и ²³⁸U для области энергий гигантского дипольного резонанса. Это позволяет описать наблюдаемые изменения пилообразного поведения выхода нейтронов из легкого и тяжелого осколков небольшим числом свободных параметров в зависимости от энергии и нуклонного состава и предсказать ν(A) для изотопов Pu . Виконана параметризацiя залежностi виходiв миттєвих нейтронiв вiд маси уламкiв ν(A) фотоподiлу актинiдних ядер ²³²Th, ²³⁵U і ²³⁸U для областi енергiй гiгантського дипольного резонансу. Це дозволяє описати спостережуванi змiни пилкоподiбної поведiнки виходiв нейтронiв з легкого i важкого уламкiв невеликим числом вiльних параметрiв у залежностi вiд енергiї та нуклонного складу, а також передбачити ν(A) для iзотопiв Pu .